Fosaprepitant for the Treatment of Refractory Postoperative Nausea and Vomiting. Issue 3 (March 2015) - Tran, Linh H.; Cudny, Magdalena; Ngo, Dat; Patel, Samit; Lam, Manuel Y.
Postoperative nausea and vomiting (PONV) is a debilitating condition that occurs in approximately 30% of patients undergoing general anesthesia. Premedication with 5-HT3 receptor antagonists and glucocorticoids is effective in clinical practice; however, 10% to 20% of patients still develop PONV. Currently, little is known about the treatment of refractory PONV. We present a case that illustrates the use of fosaprepitant for the treatment of refractory postoperative nausea and vomiting.